INTERNET LITERACY: AN ANALYSIS ON ITS POSSIBILITY - Maria Purnawati M.Pd. (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2017)
As technology emerges so fast and the demands of curriculum to integrate technology and innovation into classrooms, teachers are pushed to penetrate technology and bring the internet to everyday talks with the students. In accordance, using the euphoria of digital natives, students are also pushed to absorb and adjust themselves to growth of technology. In turn, there is no specific course on the use of the internet like the 90s curriculum had in the university level. However, the fact that not so many students bring laptop to campus everyday might indicate that they did not use the internet for learning outside classroom intensively. This study aims at describing how much internet literacy that students have. After analyzing the questionnaire descriptively, it was found that the participants of this study had poor internet literacy, in terms of the use of email, the use of social media, and the use of English in social media. Keywords: internet literacy, descriptive, poor category